Pengawasan Dinas Perhubungan terhadap Perizinan Angkutan Kota dalam Trayek Di Kota Medan - Amin Rais Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The transportation office of the city of Medan is the executing element of the Medan City government in the transportation sector which has duties in the field of public transportation services. City transportation is one of the modes of transportation that is still the focus of government reform and public transportation service providers, especially regarding the quality of services to the community. The problem in this thesis is how city transportation in the route in Medan, how the oversight mechanism is carried out by the Department of Transportation on implementation licensing of city transportation in routes in the city of Medan, what are the obstacles faced by the Medan City Transportation Agency in supervising the implementation of city transportation licenses in routes in the city of Medan. Legal arrangements for city transportation are aimed at realizing traffic and road transport safely, safely, quickly, smoothly, orderly, comfortably, and efficiently, at a cost that is affordable to the purchasing power of the community. Supervision carried out by the Department of Transportation on city transportation in Medan City is to arrange transportation facilities / infrastructure management, conduct transportation control arrangements, supervise the implementation of duties of units and UPTs in the transportation sector, make arrangements for licensing in transportation and conduct transportation violation investigations. The obstacle faced by the Department of Transportation in supervising city transportation in Medan City is that there are still personnel from the Transportation Agency who do not understand what is their duty in the field to monitor city transportation, the lack of community participation becomes a factor of weak supervision due to lack of input to the Transportation Agency so Transportation itself cannot properly evaluate